2006
DOI: 10.1111/j.1471-4159.2005.03623.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of cyclins D1 and D3 after inhibition of gap junctional communication in astrocytes

Abstract: We showed previously that the inhibition of gap junctional communication in astrocytes increased bromodeoxyuridine (BrdU) incorporation and promoted changes in the metabolic phenotype destined to fulfil the requirements of cell proliferation. In the present study we investigated the changes in the cell cycle of astrocytes promoted by the inhibition of intercellular communication through gap junctions. Thus, the presence of endothelin-1 and carbenoxolone, two gap junction uncouplers, promoted an increase in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
11

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 65 publications
3
33
0
11
Order By: Relevance
“…Thus, several authors have reported that endothelins upregulate the expression of cyclins D1 and D3, promoting the phosphorylation of pRb (Koyama et al, 2004;Tabernero et al, 2006b;Teixeira et al, 2000) required for the transition of astrocytes from the G0/G1 to the S phase of the cell cycle (Sherr, 1995). In this study, we addressed the participation of Cx43 in these effects.…”
Section: Participation Of Cx43 In the Mitogenic Effect Of Et-1mentioning
confidence: 93%
See 4 more Smart Citations
“…Thus, several authors have reported that endothelins upregulate the expression of cyclins D1 and D3, promoting the phosphorylation of pRb (Koyama et al, 2004;Tabernero et al, 2006b;Teixeira et al, 2000) required for the transition of astrocytes from the G0/G1 to the S phase of the cell cycle (Sherr, 1995). In this study, we addressed the participation of Cx43 in these effects.…”
Section: Participation Of Cx43 In the Mitogenic Effect Of Et-1mentioning
confidence: 93%
“…The protein extract (90 lg) was applied to a 10% SDS-polyacrylamide gel under reducing conditions and then transferred to a PVDF sheet as described (Tabernero et al, 2006b). The PVDF sheet was blocked with 10% fat-free dried milk in TTBS and then exposed to primary antibody against Cx43 (1:100), type I hexokinase antibody (1:500), GLUT-1 antibody (1:500), cyclin D1 (1:250), cyclin D3 (1:250), ki-67 (1:400), pRb phosphorylated on Ser-795 (1:500), or pRb phosphorylated on Ser-780 (1:200) for at least 4 h. Peroxidase-conjugated anti-rabbit IgG and peroxidase-conjugated anti-mouse IgG were used and developed with a chemiluminiscent substrate.…”
Section: Western Blottingmentioning
confidence: 99%
See 3 more Smart Citations